Sensorial Gardens: How Students of Distance Learning Biological Sciences Graduation Course at UERJ “See” These Spaces (Revista Brasileira de Pesquisa em Educação em Ciências, 2023)
The sensory garden, as a pedagogical instrument, facilitates learning and the development of environmental perceptions through the senses and their interaction with the environment for people with or without disabilities. There are no works, though, that relates the understanding of sensory gardens and distance learning students and this knowledge’s possible reverberations in teacher education. In this perspective, the present work aimed to identify the perceptions of undergraduate students finishing the Biological Sciences course at UERJ/CEDERJ polo Magé. For this purpose, an online questionnaire was applied to 35 students of the target audience to know the perceptions about the sensory garden and the senses most acute there. Afterward, a content analysis of the answers was performed. Most students understand that the sensory garden activates the senses of the body for perceptions of the environment through interaction with the plants that compose it, and that it is an inclusion tool to assist in the teaching-learning process of people with disabilities. Among the different sources of information about the sensory garden, websites/social networks predominate, followed by the university. The sensory garden of the Botanical Garden of Rio de Janeiro stands out as the most visited by the interviewees. Although the public interviewed has some perceptions about the sensory garden, these perceptions do not cover its use in education as a tool to assist the teaching practice, being necessary to deepen the debate in academic education.